Postmortem changes in lungs in severe closed traumatic brain injury complicated by acute respiratory failure - V. A. Tumanskiy; S. I. Tertnishniy (Zaporožskij Medicinskij Žurnal)
V.А. Tumanskіy, S.І. Ternishniy, L.M. Tumanskaya Pathological changes in the lungs were studied in the work of 42 patiens who died from severe closed intracranial injury (SCII). It was complicated with acute respiratory insufficient (ARI). The most modified subpleural areas were selected from every lobe of the lungs for pathological studies. Prepared histological sections were stained by means of hemotoxylin and eosin and by Van Giеson for light microscopy.